Attitude and practice of smoking among adolescent - Shrestha, Sabina; Panta, Sarita (Journal of Chitwan Medical College, 2018)
Adolescence is the time between the beginning of sexual maturation and adulthood and considered to be the period between ages 12 and 19. Smoking becomes the major risk factors for various disease and life threatening condition. The numbers of smokers are increasing day by day due to varieties of influencing factors. Therefore, a study was conducted with the objective of identifying the attitude and practice of smoking among adolescent. Descriptive exploratory study design was used to identifying the attitude and practice of smoking among adolescent towards Niharika Shishu Kunja Secondary school, Bypass, Kathmandu. Data was collected using semi structured self-administered questionnaire from 68 students studying in Niharika Shishu Kunja Secondary school. Non-probability purposive sampling was used. This study revealed that All most all (95.6%) of respondents had negative attitude towards cigarette smoking. Majority (69.1%) of respondents were non- smoker whereas 30.9% were smoker. The study concludes that adolescents were influenced to have cigarette with curiosity and experimentation with the companionship of friends.